2014
DOI: 10.1093/bja/aeu200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anaesthetic technique on the natural killer cell anti-tumour activity of serum from women undergoing breast cancer surgery: a pilot study

Abstract: NCT 041857.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(146 citation statements)
references
References 37 publications
7
121
3
2
Order By: Relevance
“…26 In contrast, a very recent study showed that lidocaine at clinically relevant concentrations of 0.01 and 0.1 mM was able to enhance NK cytolytic activity in vitro through the release of lytic granules. 27 Similar results were obtained from a pilot study of patients undergoing breast cancer resection, who had either received a regional anesthetic (paravertebral block) in combination with propofol-based total intravenous anesthesia or intravenous opioids together with a sevoflurane general anesthetic; serum from women randomized to the regional/total intravenous anesthesia group induced a greater cytolytic activity in NK cells from healthy donors than serum from women who had been administered opioids and sevoflurane, 28 indicating a possible beneficial effect of regional anesthesia and local anesthetics with respect to NK cell activity in patients undergoing (breast) cancer surgery.…”
Section: Anti-inflammatory Effects Of Local Anesthetics Potentially Asupporting
confidence: 53%
“…26 In contrast, a very recent study showed that lidocaine at clinically relevant concentrations of 0.01 and 0.1 mM was able to enhance NK cytolytic activity in vitro through the release of lytic granules. 27 Similar results were obtained from a pilot study of patients undergoing breast cancer resection, who had either received a regional anesthetic (paravertebral block) in combination with propofol-based total intravenous anesthesia or intravenous opioids together with a sevoflurane general anesthetic; serum from women randomized to the regional/total intravenous anesthesia group induced a greater cytolytic activity in NK cells from healthy donors than serum from women who had been administered opioids and sevoflurane, 28 indicating a possible beneficial effect of regional anesthesia and local anesthetics with respect to NK cell activity in patients undergoing (breast) cancer surgery.…”
Section: Anti-inflammatory Effects Of Local Anesthetics Potentially Asupporting
confidence: 53%
“…Anestezinin cerrahiden bağımsız olarak nötrofil, makrofaj, natural killer (NK) hĂŒcreleri ve dendritik hĂŒcrelerin fonksiyonlarını bozarak anjiyogenezi, enerji metabolizması, hĂŒcre proliferasyonu, apoptozis ve hĂŒcre migrasyonunu etkilediği bilinmektedir (16). Ä°nhalasyon ajanları adrenerjik aktiviteyi ve hĂŒcre içi kalsiyum konsantrasyonunu, sitokin ĂŒretimini ve postoperatif dönemde immĂŒn modĂŒlasyonu etkilerler (14).…”
Section: Discussionunclassified
“…36 A recent translational study conducted on a subset of patients enrolled in an ongoing multicentre RCT in breast cancer patients found that the serum of women (n = 10) with breast cancer randomized to receive propofol-paravertebral anesthesia for excisional surgery preserved NK immune cell cytotoxicity and breast cancer cell apoptosis to a greater extent than the serum of women randomized to receive standard volatile-based general anesthesia with opioid analgesia. 37 Practitioners may choose to promote regional anesthesia with propofol-based general anesthesia to their cancer patients for many reasons other than the possibility of an effect on cancer recurrence. The continuing prospective RCT (ClinicalTrials.gov number, NCT00418457) may prove to address whether this technique has a cause and effect link to cancer recurrence.…”
Section: Local Anesthetics and Neuraxial Anesthesiamentioning
confidence: 99%